Origin and timing of past hillslope activity in the hyper-arid core of the Atacama Desert: the formation of fine sediment lobes along the Chuculay Fault System, Northern Chile - May, Simon Matthias; Meine, Lennart; Hoffmeister, Dirk; Brill, Dominik; Medialdea, Alicia; Wennrich, Volker; Gröbner, Marie; Schulte, Philipp; Steininger, Florian; Deprez, Maxim; De Kock, Tim; Bubenzer, Olaf (Global and planetary change, 2019)
Hillslopes represent areas of predominant denudation and constitute the transition and trajectory to floodplains; they play a crucial role in understanding the long-term landscape evolution of desert environments. However, although hillslope processes are known to be very slow or even stagnant in (hyper-) arid environments, process mechanisms under the virtual absence of water are poorly understood, and process rates are essentially unknown. Based on irrigation experiments, different monitoring techniques including drone-based high-resolution digital elevation models, geomorphological, stratigraphical, geochronological (OSL), sedimentological and geochemical investigations, as well as μCT scans of sediment cores, this contribution presents detailed insights into the chronostratigraphy of tongue-shaped, 50m-long and 30m-wide fine sediment lobes located along a 10-30° steep thrust-related slope east of the Salar Grande (Atacama, Chile). Irrigation experiments were performed to gain insights into precipitation thresholds for surface runoff and hillslope dynamics. Although artificial rainfall intensities were ~46mm/h, infiltration was 100%, and the experiments did not initiate surface runoff or (detectable) slope material displacements. In addition, a distinct stratigraphic pattern with buried paleo-surfaces and paleo-biological surface crusts suggests increased hillslope activity during the late Pleistocene, potentially driven by changes of (fog-induced) humidity, salt-related shrink and swell processes, or paleo-seismic activity. While a variety of geo-bio-archives document periods of increased precipitation in the Andean parts of the Atacama Desert throughout the Quaternary, evidence for contemporaneous paleoclimatic changes from areas disconnected to Andean precipitation fluctuations (i.e., the Coastal Cordillera) is scarce. In this regard, the investigated landforms potentially represent one of only few sediment records recording paleoclimatic changes in the central desert, independent from Andean rainfall.